Oxidative Stress Biomarkers and Antioxidant Protocols - Armstrong, Donald.; Armstrong, Donald. (Methods in Molecular Biology,, 2002)
Oxidative stress has been linked to a variety of medical problems, including cardiovascular disease, cancer, arthritis, diabetes, and aging. Drawing on the growing volume of research into the impact of oxidative stress on pathophysiological mechanisms, Donald Armstrong updates and expands his highly praised Free Radical and Antioxidant Protocols (Humana, 1998) with a collection of new and valuable methods for evaluating the perturbations in cell function resulting from increased oxidative stress. Presented in a user-friendly, step-by-step format by accomplished investigators from prestigious universities, institutes, and laboratories around the world, these readily reproducible techniques cover both free radical-derived and antioxidant biomarkers. The methodologies demonstrated include ELISA, HPLC, infrared spectroscopy, gas chromatography-mass spectroscopy, immunoblotting, electroelution fractionation, isoelectric focusing, voltammetry, and electron paramagnetic resonance imaging. Special emphasis is given to the separation of complex mixtures of plant antioxidants, soft drug design to protect from toxic oxidative metabolites, in vitro oxidation conditions, and correcting for random measurement error to improve statistical interpretation. A soon-to-be-published companion volume, Oxidants and Antioxidants: Ultrastructure and Molecular Biology Protocols (Humana, 2002), contains state-of-the-art molecular and ultrastructural methods that expand the total number of protocols to 109 assays. Cutting-edge and highly practical, Oxidative Stress Biomarkers and Antioxidant Protocols provides many powerful new tools for detecting oxidative stress and for investigating the possibilities for therapeutic intervention monitoring in a variety of serious diseases.